Nutritional Assessment among Type 2 Diabetes Mellitus Patient in Southeast Asian Countries: A Scoping Review - Arifin, Noorul Aysha; Shamsudin, Juliana; Abdul Manaf, Marina; Rasudin, Syahmina; Mohd Yusoff, Siti Suhaila (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This scoping review aims to determine the available nutritional assessments for people with Type 2 Diabetes Mellitus (T2DM) in Southeast Asian countries. The methodology used for this research was based on the PRISMA-ScR standards. An extensive electronic search was carried out for papers published between 2012 and 2022 that pertained to studies conducted in Southeast Asian countries and were written in English. The eligibility criteria for this review were T2DM patients aged 20 years and older. The search was carried out using PubMed, Science Direct, Scopus, and Google Scholar databases. Hence, out of 5,445, fourteen articles met the eligibility requirements of the analysis. According to the findings, twelve studies used anthropometry measurements and biochemical tests, followed by eight studies using clinical assessments and four studies using dietary assessments. The research utilized various nutritional assessment methods such as weight, height, Body Mass Index (BMI), waist and hip circumference, body fat percentage, Fasting Blood Glucose (FBG), Glycated Hemoglobin (HbA1c), lipid profiles, Blood Pressure (BP), 3-day and 24-hour dietary recall. This review examined how the available nutritional assessments for T2DM are frequently carried out in Southeast Asian countries. The review discovered that weight, height, BMI, waist and hip circumference, FBG, HbA1c, BP, and 3-day dietary recall are the most commonly reported nutritional assessment methods.